PD1 blockade enhances K+ channel activity, Ca2+ signaling, and migratory ability in cytotoxic T lymphocytes of patients with head and neck cancer. Issue 2 (15th October 2020) - Newton, Hannah S; Gawali, Vaibhavkumar S; Chimote, Ameet A; Lehn, Maria A; Palackdharry, Sarah M; Hinrichs, Benjamin H; Jandarov, Roman; Hildeman, David; Janssen, Edith M; Wise-Draper, Trisha M; Conforti, Laura
Abstract : Background: Immunotherapy has emerged as a promising treatment modality for head and neck squamous cell carcinoma (HNSCC). Pembrolizumab, an anti-programmed death 1 antibody, is an immunotherapy agent currently approved for metastatic HNSCC and curative intent clinical trials. Although clinical responses to pembrolizumab are promising, many patients fail to respond. However, it is well known that T cell cytotoxicity and chemotaxis are critically important in the elimination of HNSCC tumors. These functions depend on ion channel activity and downstream Ca 2+ fluxing abilities, which are defective in patients with HNSCC. The purpose of this study was to elucidate the effects of pembrolizumab on potassium (K + ) channel (KCa3.1 and Kv1.3) activity, Ca 2+ fluxes, and chemotaxis in the cytotoxic T cells of patients with HNSCC and to determine their correlation with treatment response. Methods: Functional studies were conducted in CD8 + peripheral blood T cells (PBTs) and tumor infiltrating lymphocytes (TILs) from patients with HNSCC treated with pembrolizumab. Untreated patients with HNSCC were used as controls. The ion channel activity of CD8 + T cells was measured by patch-clamp electrophysiology; single-cell Ca 2+ fluxing abilities were measured by live microscopy. Chemotaxis experiments were conducted in a three-dimensional collagen matrix. Pembrolizumab patients were stratified as responders or non-responders based on pathological response (percent of viable tumor remaining at resection; responders: ≤80% viable tumor; non-responders: >80% viable tumor). Results: Pembrolizumab increased K + channel activity and Ca 2+ fluxes in TILs independently of treatment response. However, in PBTs from responder patients there was an increased KCa3.1 activity immediately after pembrolizumab treatment that was accompanied by a characteristic increase in Kv1.3 and Ca 2+ fluxes as compared with PBTs from non-responder patients. The effects on Kv1.3 and Ca 2+ were prolonged and persisted after tumor resection. Chemotaxis was also improved in responder patients' PBTs. Unlike non-responders' PBTs, pembrolizumab increased their ability to chemotax in a tumor-like, adenosine-rich microenvironment immediately after treatment, and additionally they maintained an efficient chemotaxis after tumor resection. Conclusions: Pembrolizumab enhanced K + channel activity, Ca 2+ fluxes and chemotaxis of CD8 + T cells in patients with HNSCC, with a unique pattern of response in responder patients that is conducive to the heightened functionality of their cytotoxic T cells.